2013
DOI: 10.1073/pnas.1218472110
|View full text |Cite
|
Sign up to set email alerts
|

Impairing existing declarative memory in humans by disrupting reconsolidation

Abstract: During the past decade, a large body of research has shown that memory traces can become labile upon retrieval and must be restabilized. Critically, interrupting this reconsolidation process can abolish a previously stable memory. Although a large number of studies have demonstrated this reconsolidation associated amnesia in nonhuman animals, the evidence for its occurrence in humans is far less compelling, especially with regard to declarative memory. In fact, reactivating a declarative memory often makes it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
170
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 122 publications
(195 citation statements)
references
References 58 publications
16
170
4
Order By: Relevance
“…Therefore, it would appear that the accuracy impairment in the Reminder group was contingent on the time-dependent interaction of the reminder and intervention as demonstrated in similar nonhuman animal studies (1) and widely accepted as evidence for reconsolidation (2,4,6). Consistent with the view that the Old Sequence memory trace had been rewritten by the new learning (12,17), the authors suggested that reconsolidation may have "functional significance," allowing the "continued refinement and reshaping of previously learned movement skills" (ref. 27, p. 618).…”
supporting
confidence: 53%
See 4 more Smart Citations
“…Therefore, it would appear that the accuracy impairment in the Reminder group was contingent on the time-dependent interaction of the reminder and intervention as demonstrated in similar nonhuman animal studies (1) and widely accepted as evidence for reconsolidation (2,4,6). Consistent with the view that the Old Sequence memory trace had been rewritten by the new learning (12,17), the authors suggested that reconsolidation may have "functional significance," allowing the "continued refinement and reshaping of previously learned movement skills" (ref. 27, p. 618).…”
supporting
confidence: 53%
“…The findings of our conceptual replications cast further doubt on the veracity of claims that memory updating can be mediated by reconsolidation processes (12,(14)(15)(16)(17). These experiments adhered to the canonical 3-day reconsolidation protocol and aimed to increase external validity through the use of sequences similar in structure to phone numbers or computer passwords.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations